As representações sociais de tutores da Universidade Federal do Espírito Santo - Tonini, Jefferson Muniz (2015)
This qualitative research has the objective to identify and analyze the social representations of tutors who work in distance learning courses offered through Distance Education Secretariat to the Federal University of Espirito Santo. He sought to understand how the teaching is reframed, considering the peculiarities of pedagogical practice mediated in the virtual learning environment, which decrees the break with the traditional paradigm of classroom education, based on the conduct of the teaching and learning process with the teacher and students occupy the same space and at the same time. To this end, the research questions were placed in order to unravel the imagery of the study participants about the tutoring and the actual tutorial practice. Moreover, they rose aspects related to the approach and the distance of the functions of teacher and tutor in the context of distance education now investigated, which is based on the assumptions of the System Open University of Brazil, the skills required for the performance of tutorials functions the strengths and weaknesses of mentoring. It was found, through the analysis of legislation and official documents as well as from the speeches of the interviewed subjects, teaching character tutor activity of distance learning courses. However, they showed up questions that require the appointment of possible solutions, namely the fragility of the tutor's work contract, the low pay and lack of recognition of teaching inherent in the performance of this professional education.